2022
DOI: 10.35848/1347-4065/aca258
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interdiffusion during formation of epitaxial Ca intercalated layered silicene film on its thermoelectric power factor

Abstract: Deformation of silicene buckled structure attracts great interest for the possibility of ultrahigh thermoelectric power factor. Therefore, the control method of silicene buckled structure is needed. Here, we developed the method to control composition ratio in epitaxial Ca intercalated layered silicene (CaSi2) film formed by solid phase epitaxy through an atomic interdiffusion between Ca films and Si substrate because of the possible existence of the relation between silicene buckled structure in CaSi2 film an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Then the lattice misfit at the interface of the CaSi 2 film and Si(111) substrate is discussed. The orientation relationship between the Si(111) substrate and the epitaxial CaSi 2 film (or grains) in the present work was (001) CaSi2 //(111) Si , [1][2][3][4][5][6][7][8][9][10] CaSi2 // Si , and [001] CaSi2 //[111] Si . Thus, the lattice misfit is calculated from the lattice parameter, a, for each CaSi 2 phase and the d 110 lattice spacing of the Si substrate.…”
mentioning
confidence: 66%
“…Then the lattice misfit at the interface of the CaSi 2 film and Si(111) substrate is discussed. The orientation relationship between the Si(111) substrate and the epitaxial CaSi 2 film (or grains) in the present work was (001) CaSi2 //(111) Si , [1][2][3][4][5][6][7][8][9][10] CaSi2 // Si , and [001] CaSi2 //[111] Si . Thus, the lattice misfit is calculated from the lattice parameter, a, for each CaSi 2 phase and the d 110 lattice spacing of the Si substrate.…”
mentioning
confidence: 66%
“…31,32) In this previous study, the compositional analysis revealed the formation of Si-rich CaSi 2 films, indicating that the deformation of the buckling structure could be related to non-stoichiometry. 33,34) Therefore, controlling atom species, elemental composition and strain near the interface, etc., can largely deform the buckling structure, leading to ultrahigh S 2 σ. Among Caintercalated group IV 2D materials, CaGe 2 can exhibit higher TE performance than CaSi 2 because the theoretical study reported that germanene could have higher μ than silicene.…”
mentioning
confidence: 99%